Perception and Facts Regarding Electroconvulsive Therapy at Benazir Bhutto Hospital, Rawalpindi - Muhammad Azeem Rao; Fareed Aslam Minhas; Shumaila Tasleem; Syed Rafay Hussain Zaidi; Bahjat Najeeb; Manzoor Ali (Journal of Rawalpindi Medical College)
Objective: This study delves into the effectiveness of Electroconvulsive Therapy (ECT) as a treatment for psychiatric disorders, focusing on its administration protocols, patient demographics, and therapeutic outcomes.